Factors associated with measles antibody titers in children aged 12-36 months in Indonesia: an analysis of National Health Research 2013 - Ni Ketut Aryastami; Prisca Petty Arfines; Vivi Setiawaty; Siti Isfandari (Sekretariat Badan Penelitian dan Pengembangan Kesehatan, 2021)
Background: The immunization program in Indonesia has been implemented since 1956 started to eradicate smallpox and expanded until 1980, including Measles. The timely and complete implementation of basic immunization is the main strategy to protect the population, including outbreak prevention. The purpose of this study is to determine the level immunity of Measles antibody as the outcome of completed basic immunization and its contributors in children aged 12-36 months. Methods: This study is a secondary data analysis of the Indonesia Basic Health Survey (RISKESDAS) 2013. The analysis was carried out on a serological sample of the antibody titer of children aged 12-36 months, totaling 229 samples. The sample inclusion criteria were children who had complete sociodemographics data, basic immunization records and Measles antibody titer data. Measles examination was carried out using the Enzyme-Linked Immunosorbent Assay (ELISA) method. Results: Incomplete immunization, being a boy, and lack of cleanliness in the family room were significantly associated with lower measles antibody levels in children. Having each variable controlled, completeness of immunization (OR=1,99; p=0.018; 95% CI=1.124-3.544) and gender of boy (OR=2.0; p=0.016; 95% CI=1.137-3.515) remain as significant variables for antibody’s titer. Conclusion: The completeness of immunization has a significant association towards titer antibody of Measles in children. Immunization completeness is an actual effort to reach herd immunity in children and to prevent measles outbreak in the community. Adequate health promotion is needed to change people's behavior to believe in the safety and importance of implementing complete basic immunization for children even in pandemic conditions. Keywords: antibody titer, immunization, children aged 12-36 months, Indonesia, measles Abstrak Latar belakang: Program imunisasi di Indonesia telah dilaksanakan sejak tahun 1956 yang dimulai dengan pemberantasan cacar yang diperluas hingga tahun 1980, termasuk campak. Pelaksanaan imunisasi dasar yang tepat waktu dan lengkap merupakan strategi utama untuk perlindungan penduduk, termasuk pencegahan Kejadian Luar Biasa (KLB). Tujuan dari penelitian ini untuk mengetahui tingkatan kekebalan antibodi Campak sebagai hasil dari kelengkapan imunisasi dasar dan faktor yang berkontribusi pada anak usia 12-36 bulan. Metode: Penelitian ini merupakan analisis data sekunder Riset Kesehatan Dasar Indonesia (RISKESDAS) 2013. Analisis dilakukan pada sampel serologi titer antibodi anak usia 12-36 bulan yang berjumlah 229 sampel. Kriteria inklusi sampel adalah anak yang memiliki data sosiodemografi lengkap, catatan imunisasi dasar dan data titer antibodi Campak. Pemeriksaan campak dilakukan dengan metode Enzyme-Linked Immunosorbent Assay (ELISA). Hasil: Imunisasi yang tidak lengkap, berjenis kelamin laki-laki, dan kurangnya kebersihan di ruang keluarga berhubungan bermakna dengan rendahnya tingkat antibodi campak pada anak. Setelah masing-masing variabel terkontrol, kelengkapan imunisasi (OR=1,99; p=0,018; 95% CI=1.124-3.544) dan jenis kelamin laki-laki (OR=2.0; p=0.016; 95% CI=1.137-3.515) merupakan variabel yang tetap berhubungan dengan titer antibodi secara signifikan. Kesimpulan: Kelengkapan imunisasi memiliki hubungan yang bermakna terhadap titer antibodi Campak pada anak. Kelengkapan imunisasi merupakan upaya nyata untuk mencapai herd immunity pada anak dan mencegah wabah campak di masyarakat. Promosi kesehatan yang memadai diperlukan untuk mengubah perilaku masyarakat agar percaya akan keamanan dan pentingnya pelaksanaan imunisasi dasar lengkap bagi anak meskipun dalam kondisi pandemi. Kata kunci: titer antibodi, imunisasi, anak usia 12-36 bulan, Indonesia, campak